Role of registered nurses in error prevention, discovery and correction. Issue 2 (2nd April 2008) - Rogers, A E; Dean, G E; Hwang, W-T; Scott, L D
Abstract : Background: Registered nurses have a vital role in discovering and correcting medical error. Objective: To describe the type and frequency of errors detected by American critical care nurses, and to ascertain who made the errors discovered by study participants. Methods: Daily logbooks were used to collect information about errors discovered by a random sample of 502 critical care nurses during a 28-day period. Results: Although the majority of errors discovered and corrected by critical care nurses involved medications (163/367), procedural errors were common (n = 115). Charting and transcription errors were less frequently discovered. The errors discovered by participants were attributed to a wide variety of staff members including nurses, doctors, pharmacists, technicians and unit secretaries. Conclusions: Given the importance of nurses in maintaining patient safety, future studies should identify factors that enhance their effectiveness to prevent, intercept and correct healthcare errors.